2012
DOI: 10.1021/jp210825x
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Purple Membrane Variants for the Construction of Highly Oriented Membrane Assemblies on the Basis of Noncovalent Interactions

Abstract: Purple membranes (PM) from Halobacterium salinarum have been discussed for several technical applications. These ideas started just several years after its discovery. The biological function of bacteriorhodopsin (BR), the only protein in PM, is the light-driven proton translocation across the membrane thereby converting light energy into chemical energy. The astonishing physicochemical robustness of this molecular assembly and the ease of its isolation triggered ideas for technical uses. All basic molecular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The membrane is clearly detected by displaying the two surface potential levels of 0 mV and −9 mV relative to the silicon substrate, which reflects the potential difference between the CP side and the EC side of PM. It is known that the potential of the CP side of PM is 8–10 mV higher than that of the EC side [23,36]. Therefore, dark blue patches can be attributed to the EC side facing upward and the lower contrast patches can be attributed to the CP side facing upward.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane is clearly detected by displaying the two surface potential levels of 0 mV and −9 mV relative to the silicon substrate, which reflects the potential difference between the CP side and the EC side of PM. It is known that the potential of the CP side of PM is 8–10 mV higher than that of the EC side [23,36]. Therefore, dark blue patches can be attributed to the EC side facing upward and the lower contrast patches can be attributed to the CP side facing upward.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous applications can be employed based on its energy conversion and photoelectrism properties [40,41]. Several different approaches have been explored and applied for directional PM assembly in device configurations in the past with varying degrees of success, such as chemical assembly [42], electric field sedimentation [43], and BR mutation [36]. In order to directionally assemble PM on solid substrate and make functional devices, de novo peptides were employed to modify the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[71][72][73] While the exact mechanism of cubic membrane formation is still not fully resolved, recent studies have identified several key components, such as conical phospholipids, 74,75 cholesterol molecules 76 and membrane proteins. 71,[77][78][79][80][81] Conical lipids have packing parameters greater than one and induce negative curvature within the lipid bilayer. The lipid's head and splayed chains form a wedge in the bilayer, 82 facilitating the formation of gyroid and diamond-structured lattices.…”
Section: Photonic Structure-formation Pathways In Biologymentioning
confidence: 99%
“…Bacteriorhodopsin belongs to the class of biological reversible photosensitive media. It has been widely investigated for use in many technological applications such as real‐time holography , erasable optical storage , light modulation , etc. The optical properties of BR, which define the possible applications, can be modified by changing its environment (matrix, chemical additives, temperature, etc.…”
Section: Introductionmentioning
confidence: 99%